Elevating microRNA-122 in blood improves outcomes after temporary middle cerebral artery occlusion in rats. Issue 8 (August 2016) - Liu, Da Zhi; Jickling, Glen C; Ander, Bradley P; Hull, Heather; Zhan, Xinhua; Cox, Christopher; Shroff, Natasha; Dykstra-Aiello, Cheryl; Stamova, Boryana; Sharp, Frank R
Because our recent studies have demonstrated that miR-122 decreased in whole blood of patients and in whole blood of rats following ischemic stroke, we tested whether elevating blood miR-122 would improve stroke outcomes in rats. Young adult rats were subjected to a temporary middle cerebral artery occlusion (MCAO) or sham operation. A polyethylene glycol-liposome-based transfection system was used to administer a miR-122 mimic after MCAO. Neurological deficits, brain infarction, brain vessel integrity, adhesion molecule expression and expression of miR-122 target and indirect-target genes were examined in blood at 24 h after MCAO with or without miR-122 treatment. miR-122 decreased in blood after MCAO, whereas miR-122 mimic elevated miR-122 in blood 24 h after MCAO. Intravenous but not intracerebroventricular injection of miR-122 mimic decreased neurological deficits and brain infarction, attenuated ICAM-1 expression, and maintained vessel integrity after MCAO. The miR-122 mimic also down-regulated direct target genes (e.g. Vcam1, Nos2, Pla2g2a) and indirect target genes (e.g. Alox5, Itga2b, Timp3, Il1b, Il2, Mmp8) in blood after MCAO which are predicted to affect cell adhesion, diapedesis, leukocyte extravasation, eicosanoid and atherosclerosis signaling. The data show that elevating miR-122 improves stroke outcomes and we postulate this occurs via downregulating miR-122 target genes in blood leukocytes.